Über den lokalen Greuzwertsatz für Dichtefunktionen - Survila, P. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:П. Сурвила. О локальной предельной теореме для плотностейP. Survila. Apie ribinę lokalinę teoremą tankiams